Perceived image quality with simulated segmented bifocal corrections: publisher’s note - Dorronsoro, Carlos (Biomed Opt Express, 2016)
This publisher’s note amends the author affiliations of a recent publication [Biomed. Opt. Express 7, 4388 (2016)].